2013
DOI: 10.7322/abcshs.v38i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Panorama internacional e nacional da estratégia do tratamento diretamente supervisionado (DOTS) nas políticas de controle da tuberculose

Abstract: A tuberculose é uma doença infecciosa de grande impacto social causada pelo Mycobacterium tuberculosis. O relatório da Organização Mundial da Saúde (OMS) 2010 estima em 14 milhões o número de pessoas com tuberculose no mundo, com concentração crescente nos países com baixo desenvolvimento social. Em 1993, a OMS lançou o Tratamento Diretamente Supervisionado de Curto Prazo (DOTS), considerado a estratégia mais efetiva no controle da tuberculose em grandes proporções. O DOTS foi introduzido no Brasil em 1998, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
10

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 8 publications
0
9
0
10
Order By: Relevance
“…In the first discursive block, it is observed that the health professional (MS1), taking the position of manager, is questioned by the circulating senses anchored in the speech that Mozambique is one of the countries with critical problems of laboratories, infrastructures and modern technologies (1,13) . The lack of sufficient laboratories in Sub-Saharan Africa, of which Mozambique is a part, seriously compromises the detection and reporting of TB cases (1,8,13) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the first discursive block, it is observed that the health professional (MS1), taking the position of manager, is questioned by the circulating senses anchored in the speech that Mozambique is one of the countries with critical problems of laboratories, infrastructures and modern technologies (1,13) . The lack of sufficient laboratories in Sub-Saharan Africa, of which Mozambique is a part, seriously compromises the detection and reporting of TB cases (1,8,13) .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of sufficient laboratories in Sub-Saharan Africa, of which Mozambique is a part, seriously compromises the detection and reporting of TB cases (1,8,13) . It should be noted that this reality is also present in other countries with high TB burden, such as Nigeria, South Africa and Zimbabwe (1) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of this strategy presents some challenges, related to the organization and management of health services, the geopolitical context, and the long period of adaptation required among health professionals and local governments. However, improvements related to this policy can be observed in the TB control indicators, particularly among vulnerable populations such as homeless people, injecting drug addicts and alcoholics (3)(4) . The success of the DOT transfer as a policy is directly related to three dimensions: the information about the DOT received by the professionals who will implement this policy; the knowledge of these professionals about the policy; and innovation, or mode of implementation, of this new policy/ action (5) .…”
Section: Introductionmentioning
confidence: 99%